A Case Report of the Atypical Manifestation of Diverticular Disease: Giant Colonic Diverticulum - Oriana Nogueira; Mariana Lemos; Mariana Duque; Catarina Lopes; Eva Santos; Miguel Fernandes (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
In this study we intend to present a case of a rare complication of diverticular disease. The diagnosis is primarily made by CT because the symptoms are vague. To prevent perforation or other consequences, a surgical resection is the advised course of action. In this case, a 74-year-old woman complained of intestinal obstruction and an acute abdomen and went to the emergency department. Physical examination showed a distended abdomen, diffusely painful on palpation, with a positive Blumberg sign, no hernias. An abdominal computed tomography (CT) discovered a mesenteric collection with 60mm and air-fluid level compatible with an abscess, adjacent to a small bowel loop. An emergency laparotomy was done, which disclosed a 6cm cystic formation dependent on the sigmoid colon in the antimesentery border, which was removed en bloc with the neighboring colon. It was identified by the specimen as a type 2 diverticulum. After a typical postoperative period, the patient was discharged.